The Coral Trait Database, a curated database of trait information for coral species from the global oceans (vol 3, 160017, 2016) - Madin, J.; Anderson, K.; Andreasen, M.; Bridge, T.; Cairns, S.; Connolly, S.; Darling, E.; Diaz, M.; Falster, D.; Franklin, E.; Gates, R.; Harmer, A.; et al. (Nature Publishing Group, 2017)
This corrects the article DOI: 10.1038/sdata.2016.17.